Research in the main Incahuasi ushnu, Cañete: contributions to the study of Inca ushnus - Chu, Alejandro (2017)
The archaeological site of Incahuasi, located in the middle valley of the Cañete river, in the south-central coast of Peru, has often been mentioned in the archaeological literature; however, studies in the settlement have been superficial to date. Recent research conducted in sector E have shown the constructive complexity of the ushnu in the main square of the site and at least three construction phases associated with changes in size and orientation have been identified. Excavations of the main ushnu show the complex occupation of the site, which was developed during a much longer time than those mentioned in colonial documents.